The Effect of Financial Knowledge, Financial Attitudes and Financial Management Behavior on Financial Satisfaction of Gopay Fintech Users in Malang City - Dewi, Ria Rahmawati; Mursidi; Warsono (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study aims to determine the effect of financial knowledge, financial attitude and financial management behavior on financial satisfaction among fintech gopay users in Malang city. The number of samples in this study were 100 respondents with a purposive sampling method. The object of this research is the people of Malang city. The data analysis method used is multiple linear regression with SPSS 25 software. The results of this study indicate that the three independent variables, namely financial knowledge, financial attitudes and financial management behavior simultaneously and partially influence financial satisfaction.